Hidden Drivers of Greenhouse Gas Emissions: Exploring Business Travel and Employee Commuting's Role in Climate Change - Noor, Muhammad Zainuddin; Purnaweni, Hartuti; Hidayat, Jafron Wasiq (Formosa Journal of Science and Technology, 2024)
This research examines the impact of business travel and employee commuting on greenhouse gas (GHG) emissions in a growing telecommunications company in Indonesia. Utilizing quantitative descriptive analysis, the research relies on the company's secondary data to quantify emissions, adhering to Tier 1 standards set by the Intergovernmental Panel on Climate Change (IPCC). The findings reveal that these activities contribute to the company's GHG emissions, amounting to 143,291 tCO2e, highlighting the role of business travel and employee commuting as drivers of emissions.